Dampak Pernikahan Usia Dini pada Keharmonisan Rumah Tangga (Jurnal Ilmu Pendidikan Keagamaan Kristen : Arastamar, 2025)
This study aims to analyze the impact of early marriage on household harmony from a Christian faith perspective. The main issue examined is how marriage at an immature age affects the dynamics of the husband-wife relationship, emotional stability, and the overall quality of family life. The research method employed is a literature study using a descriptive qualitative approach, in which theological, psychological, and sociological literature serve as the primary sources of analysis. The novelty of this research lies in the integration of Christian faith values in assessing an individual's readiness for marriage as a sacred covenant rather than merely a social contract. The findings indicate that early marriage poses a high risk of household disharmony due to emotional immaturity, economic instability, and a lack of spiritual understanding. The study concludes that faith formation and character education based on Christian values are essential from adolescence to prevent early marriage and to build families that are spiritually, emotionally, and socially resilient.